2017
DOI: 10.1080/02713683.2016.1266661
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Choroidal Thickness and Retinal Nerve Fiber Layer in Untreated Patients with Obstructive Sleep Apnea-Hypopnea Syndrome: A Case–Control Study

Abstract: In OSAHS patients, PPCT, CMCT, and RNFL were significantly thinner compared with the control group. These results may explain why OSAHS patients are prone to normotensive glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…This highly vascularized nature of the choroid, which can be assessed by non-invasive imaging, has drawn attention to the choroid in a variety of systemic diseases, such as the metabolic, inflammatory, and the systemic vascular disease ( 88 ). Peripapillary CT measurements have also been attempted in patients with systemic illnesses ( 24 , 89 93 ) such as diabetes ( 23 , 94 97 ), thyroid diseases ( 98 , 99 ), and pulmonary diseases ( 25 , 100 ) ( Table 3 ). Yazgan et al ( 94 ) showed that the macular and peripapillary choroid was significantly thicker in pre-diabetic patients than in healthy controls at all 15 measuring points.…”
Section: Choroidal Thickness Measurement Beyond the Maculamentioning
confidence: 99%
See 1 more Smart Citation
“…This highly vascularized nature of the choroid, which can be assessed by non-invasive imaging, has drawn attention to the choroid in a variety of systemic diseases, such as the metabolic, inflammatory, and the systemic vascular disease ( 88 ). Peripapillary CT measurements have also been attempted in patients with systemic illnesses ( 24 , 89 93 ) such as diabetes ( 23 , 94 97 ), thyroid diseases ( 98 , 99 ), and pulmonary diseases ( 25 , 100 ) ( Table 3 ). Yazgan et al ( 94 ) showed that the macular and peripapillary choroid was significantly thicker in pre-diabetic patients than in healthy controls at all 15 measuring points.…”
Section: Choroidal Thickness Measurement Beyond the Maculamentioning
confidence: 99%
“…Regarding peripapillary CT in patients with pulmonary diseases, Ozcimen et al ( 25 ) showed that subfoveal and peripapillary CT in patients with chronic obstructive pulmonary disease tended to be lower than those in the healthy control group, however, the difference was not statistically significant. Yazgan et al ( 100 ) measured subfoveal and peripapillary CT in patients with sleep apnea-hypopnea syndrome and normal controls and found that subfoveal CT was lower in all sleep apnea-hypopnea syndrome subgroups than in the control group. However, peripapillary CT in all sectors was lower only in the moderate and severe subgroups than in the healthy controls.…”
Section: Choroidal Thickness Measurement Beyond the Maculamentioning
confidence: 99%
“…Numerous studies have reported significant reduction, while other studies have found no difference in RNFL thickness in OSA patients compared to normal controls [118,[121][122][123][164][165][166][167][168][169][170][171][172][173]. Recently, numerous meta-analyses have been published, in which all found a significant reduction of average RNFL thickness in OSA patients [122,123,166,167,174].…”
Section: Retinal Nerve Fiber Layer and Ganglion Cell Layermentioning
confidence: 99%
“…In OSA, an increase in potent vasoconstrictors such as endothelin, contribute to macro and microvascular damage. Indeed, published data has confirmed thinning of the retinal nerve fiber layer (RNFL) in participants with OSA [ 31 47 ]. Similar to peripheral nerves, it is thought that hypoxic damage during sleep and vascular dysregulation drive RNFL thinning in OSA [ 32 , 48 ].…”
Section: Introductionmentioning
confidence: 99%